Colonnades of the Agricultural Building, Alaska-Yukon-Pacific Exposition, Seattle, Washington, ca. 1909 - University of Washington Libraries. Special Collections Division (1909)
Caption on image: Colonades of the Agricultural Building, Alaska, Yukon, Pacific Exposition, 1909, Seattle, Wash. (Official Post Card) Publisher: Portland Post Card Co. PH Coll 433.27 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number